The tourism and hospitality career progression pathway - Alexander Preko; Hod Anyigba (International Hospitality Review)
Purpose – The aim of this study was to conduct a comprehensive investigation into declining and emerging occupations and job titles and to develop a national career progression pathway for the tourism and hospitality (T&H) sector. Design/methodology/approach – Anchored on the Social Cognitive Career Theory, this study used face to face in-depth interviews of 33 industry stakeholders: policymakers, trade association, training providers and beneficiaries (T&H). Findings – The finding reveals that only the “watchman” occupation was identified as the declining job while majority of the emerging jobs were more related to information technology and environmental occupations (website designers, digital marketers, data analysts, hygienists, and safety and hazard experts). Practical implications – The findings provide a valuable signal for the growing number of jobs in security services, hygiene and information technology-oriented occupations, which the Ministry of Tourism, Arts and Culture including practitioners including HR directors and general managers should respond timely to and to these growing needs in order to remain competitive in the sector. Originality/value – This is the first study in context that responded to a call by industry players to fill in a practical knowledge gap in examining declining and emerging jobs and job titles in the T&H sector. The study provides vocational insights into mapping the entry level requirements for the jobs allied with occupations in the national technical and vocational educational training qualifications framework of Ghana at the national level.